Code red : an economist explains how to revive the healthcare system without destroying it - Dranove, David (Princeton University Press, 2008)
The U.S. healthcare system is in critical condition--but this should come as a surprise to no one. Yet until now the solutions proposed have been unworkable, pie-in-the-sky plans that have had little chance of becoming law and even less of succeeding. In Code Red, David Dranove, one of the nation's leading experts on the economics of healthcare, proposes a set of feasible solutions that address access, efficiency, and quality. Dranove offers pragmatic remedies, some of them controversial, all of them crucially needed to restore the system to vitality. He pays special attention to the plight of.